Pediatric Gastroenterologists' Approach to Venous Thromboembolism Prophylaxis in Pediatric Inflammatory Bowel Disease. Issue 2 (February 2018) - Chien, Kimberley A.; Hammad, Hoda T.; Gerber, Linda; Sheth, Sujit; Sockolow, Robbyn; Kucine, Nicole
Abstract : ABSTRACT: The risk of venous thromboembolism (VTE) is significantly increased in patients with inflammatory bowel disease (IBD). For the adult population, prophylaxis guidelines exist to help guide physicians in their management of high-risk IBD patients. Although it is known that children with IBD also experience increased rates of VTE, there is no clear consensus on how best to prevent these unwanted complications. We sought to better understand practicing pediatric gastroenterologists' awareness of this issue and practices surrounding prevention of VTE in their pediatric patients. We found that pediatric gastroenterologists are well aware of the increased risk for VTE in children with IBD, that anticoagulant prophylaxis is infrequently used for pediatric patients, and that the most commonly cited reason for not providing prophylaxis is the lack of available guidelines in the literature. Abstract : Supplemental Digital Content is available in the text